Enhanced thermoelectric performance of P-type CaMg2Bi1.98 and optimized CaAl2Si2-type Zintl phase module with equal cross-section area. (December 2020) - Guo, Muchun; Zhu, Jianbo; Guo, Fengkai; Zhang, Qian; Cai, Wei; Sui, Jiehe
Abstract: Recently, Zintl phase Mg3 Sb2 has displayed superior n-type thermoelectric properties. However, the corresponding p-type thermoelectric materials with high thermoelectric properties are still in urgent need. CaMg2 Bi2 -based Zintl compound attracts increasing enthusiasm in recent years due to its high carrier mobility and low lattice thermal conductivity. Here, Yb is used to replace Ca to further tune thermoelectric transport behavior of CaMg1.9 Zn0.1 Bi1.98, an optimized composition according to previous work. The synergistic effect of the enhanced carrier concentration caused by electronegativity difference in cation site and the suppressed lattice thermal conductivity induced by the stronger point defects scattering leads to the peak ZT of 1.0 in Ca0.65 Yb0.35 Mg1.9 Zn0.1 Bi1.98, which exceeds most of reported CaMg2 Bi2 -based materials. The maximum ZT eng of single p-type leg Ca0.65 Yb0.35 Mg1.9 Zn0.1 Bi1.98 is up to 0.54 between T c = 300 K and T h = 773 K, catching up with the current highest level in 1-2-2 Bi-based materials. Moreover, the interrelationship between conversion efficiency and p-n pair cross-section area ratio ( A n /A p ) is considered. For n-type Mg3.1 Co0.1 Sb1.5 Bi0.49 Te0.01 /p-type Ca0.65 Yb0.35 Mg1.9 Zn0.1 Bi1.98 pair, a maximum conversion efficiency of 12% is obtained at the optimum A n /A p approaching to 1. This prominent conversion efficiency and equal cross-section area facilitate the module fabrication process and exhibit bright prospect of CaMg2 Bi2 -based thermoelectric materials. Graphical abstract: Image 1 Highlights: Carrier concentration and mobility of CaMg2 Bi2 system boost simultaneously. Intensive point defects scattering results in decreased κ L . The peak ZT of 1.0 and the maximum ZT eng of 0.54 are presented. The highest η of 12% is gained in p-n pair with the optimum An /Ap ≈ 1.